A Facility-Based Cross-Sectional Study on the Implementation of the IMNCI Program in Public Health Centers of Soro District, Hadiya Zone, Southern Ethiopia - Gintamo B; Azhar Khan M; Gulilat H; Mekonnen Z; Kumar Shukla R; Malik T (Dove Medical Press, 2020)
Binyam Gintamo,1 Mohammed Azhar Khan,1 Henok Gulilat,1 Zeleke Mekonnen,2 Rakesh Kumar Shukla,1 Tabarak Malik3 1Department of Biotechnology, Faculty of Applied Sciences and Biotechnology, Shoolini University, Bajhol, HP, India; 2School of Medical Laboratory Sciences, Institute of Health, Jimma University, Jimma, Ethiopia; 3Department of Biochemistry, College of Medicine & Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tabarak Malik Email malikitrc@gmail.comBackground: Integrated Management of Neonatal and Childhood Illnesses (IMNCI) is one of the child health programs and it provides an integrated approach and focuses on the well-being of the whole child. Globally, nearly nine million children pass away every year with preventable and treatable conditions. IMNCI program is provided by the health facilities to aid children under five years of age from illness. This study is aimed at assessing the implementation of the IMNCI program in public health centers of Soro District, Hadiya Zone, Southern Ethiopia.Methods: The implementation of the IMNCI program was studied using a facility-based cross-sectional study design integrating both qualitative and quantitative data collected from 9 public health centers in Soro district, Hadiya Zone, Southern Ethiopia. A total of 390 (92%) caregivers were included in the study by the proportion of under-five outpatient coverage from each public health center. Data were collected through face to face interviewer-administered questionnaires, document review checklist, observation checklist, and in-depth interview guide.Results: Based on agreed criteria resources’ availability was 80.11% and judged as fair. Less than 50% of health centers (HCs) had cotrimoxazole and gentamycin. The compliance of health workers was 85.5% and judged as good. Below 85% of prescribed drugs were given correctly for the classified disease. Counseling on medication and follow updates were given for less than 80% of caretakers. The overall satisfaction of clients on IMNCI was 79.5% according to the judging criteria. The caretakers who took less than 30 minutes to reach the health center on foot (AOR=7.7, 95% CI [3.787– 15.593]), caretakers who waited for less than 30 minutes to see the health care provider (AOR=2, 95% CI [1.00– 3.77]), the caretakers who found prescribed drugs in HCs pharmacy (AOR = 3.7,95% CI [1.91– 7.34]), the caretakers who have less than four family size (AOR=2, 95% [1.109– 4.061]) were more satisfied in IMNCI services, whereas, caregivers who measured the weight of child were negatively associated with satisfaction (AOR= 0.24, 95% CI [0.13– 0.45]).Conclusion: This study found that the overall implementation of the Integrated Management of Neonatal and Childhood Illnesses was good. All health centers had trained health workers, ORS, paracetamol, vitamin A, chart booklet, and IMNCI guidelines were available; however, cotrimoxazole, gentamycin, ampicillin, and mebendazole were less abundant drugs in health centers. Further, a large-scale study is required to be conducted in future in other districts to ensure proper implementation of the IMNCI program in Ethiopia.Keywords: IMNCI, healthcare provider, practice, Hadiya zone, southern Ethiopia